2011
DOI: 10.1038/ijo.2011.144
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of weight loss with laparoscopic adjustable gastric banding: induction of satiety not restriction

Abstract: Laparoscopic adjustable gastric banding (LAGB) has rapidly emerged as a popular bariatric procedure because of its safety, efficacy, durability and adjustability. Despite widespread use, there is limited understanding of how it induces weight loss. Previously, it has been classified as a restrictive procedure, physically limiting the patient to a small meal that subsequently slowly empties into the distal stomach. However, the tiny pouch of stomach created above the LAGB appears to be unable to accommodate eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…Surprisingly, despite different gastric volumes between the groups, we did not observe any difference concerning daily caloric intake at any point of the follow-up in the subjects with or without sleeve dilatation. Burton et al already reported that weight loss after surgery was mainly due to satiety and not to food restriction [14]. These results are also in accordance with the study of Gras-Miralles et al which showed that caloric intake capacity was similarly reduced after RYGBP and LSG, despite a smaller gastric pouch in RYGBP (30 vs 150 ml) [15].…”
Section: Discussionsupporting
confidence: 92%
“…Surprisingly, despite different gastric volumes between the groups, we did not observe any difference concerning daily caloric intake at any point of the follow-up in the subjects with or without sleeve dilatation. Burton et al already reported that weight loss after surgery was mainly due to satiety and not to food restriction [14]. These results are also in accordance with the study of Gras-Miralles et al which showed that caloric intake capacity was similarly reduced after RYGBP and LSG, despite a smaller gastric pouch in RYGBP (30 vs 150 ml) [15].…”
Section: Discussionsupporting
confidence: 92%
“…How the LAGB induces weight loss is not fully understood 4. Initially, weight loss was attributed to eating in small proportions since the pouch fills rapidly and passage to the distal stomach is limited 4 5.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, weight loss was attributed to eating in small proportions since the pouch fills rapidly and passage to the distal stomach is limited 4 5. Although unable to identify specific changes, Dixon et al 6 emphasised that the band compresses the cardia, altering neuronal and hormonal-induced satiety and decreasing appetite.…”
Section: Introductionmentioning
confidence: 99%
“…One way is passive, in other words, when the stomach fills and hunger hormone levels drop, hunger decreases and satiety is experienced as the absence of hunger [38]. Another way is through the stretching of the stomach neurons as the stomach gets full [39]. Stomach muscles stretch triggering afferent neurons that then send signals to the brain to [39].…”
Section: Anorexigenic Forcesmentioning
confidence: 99%
“…Another way is through the stretching of the stomach neurons as the stomach gets full [39]. Stomach muscles stretch triggering afferent neurons that then send signals to the brain to [39].…”
Section: Anorexigenic Forcesmentioning
confidence: 99%